2023
DOI: 10.3847/1538-4365/acad7a
|View full text |Cite
|
Sign up to set email alerts
|

A Three-dimensional Map of the Milky Way Using 66,000 Mira Variable Stars

Abstract: We study the three-dimensional structure of the Milky Way using 65,981 Mira variable stars discovered by the Optical Gravitational Lensing Experiment survey. The spatial distribution of the Mira stars is analyzed with a model containing three barred components that include the X-shaped boxy component in the Galactic center (GC) and an axisymmetric disk. We take into account the distance uncertainties by implementing the Bayesian hierarchical inference method. The distance to the GC is R 0 = 7… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 123 publications
0
13
0
Order By: Relevance
“…Further, the lack of precise and accurate distance estimates, interstellar extinction, variability-related, and period-magnitude-relation uncertainties have an almost equally large impact, especially in the K s band. We note again that neither Gaia parallaxes nor the PLR-derived distance from Iwanek et al (2023) are well suited to these distant stars near the plane with significant envelopes.…”
Section: Error Budget Of Circumstellar Extinction Valuesmentioning
confidence: 69%
See 2 more Smart Citations
“…Further, the lack of precise and accurate distance estimates, interstellar extinction, variability-related, and period-magnitude-relation uncertainties have an almost equally large impact, especially in the K s band. We note again that neither Gaia parallaxes nor the PLR-derived distance from Iwanek et al (2023) are well suited to these distant stars near the plane with significant envelopes.…”
Section: Error Budget Of Circumstellar Extinction Valuesmentioning
confidence: 69%
“…Of course this sample selection method depends on a different set of assumptions, namely that high velocity (>100 km s −1 ) Mira variables within 4 degrees of l,b=0,0 are at the distance of the GC, i.e., 8 kpc from the Sun (i.e., Gravity Collaboration et al 2019;Reid et al 2019;Do et al 2019;Iwanek et al 2023). We note that reliable Gaia data is sparse for this sample given the proximity to the Galactic plane and the large distances.…”
Section: Data and Sample Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Asymptotic giant branch (AGB) stars are in the late stages of stellar evolution and, due to their mass loss, are dominating contributors to the cosmic gas/dust cycle (e.g., Höfner & Olofsson 2018). With typical ages of a few gigayears (e.g., Sevenster 1999;Höfner & Olofsson 2018), AGB stars are found in all structures of the Milky Way 9 including the Galactic thin disk, thick disk, bulge, halo, and even the tidal stellar streams produced by the interaction of the Milky Way with its satellites (e.g., Li et al 2019;Suh 2021;Iwanek et al 2023). The three-dimensional (3D) motions of AGB stars located off the Galactic disk can provide a crucial clue on their nature, potentially shedding light on the formation history of our Galaxy.…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies have used SRVs and Miras to probe the structure of the Milky Way (Trabucchi et al 2017(Trabucchi et al , 2019(Trabucchi et al , 2021Iwanek et al 2023), and demonstrated that calibrated PL sequences can yield distances to within 15% precision (Tabur et al 2010;Auge et al 2020). However, sample sizes have so far remained limited and did not include pulsation amplitudes as an additional constraint (which increases the distance precision further; Rau et al 2019).…”
Section: Introductionmentioning
confidence: 99%